SKIN-TO-SKIN CONTACT AND BREASTFEEDING AT CHILDBIRTH: WOMEN'S DESIRES, EXPECTATIONS, AND EXPERIENCES - Alice Parentes da Silva Santos; Zeni Carvalho Lamy; Maria Eduarda Koser; Clarice Maria Ribeiro de Paula Gomes; Beatriz Matos Costa; Laura Lamas Martins Gonçalves (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To analyze women's desires, expectations and experiences regarding skin-to-skin contact and breastfeeding in the first hour of life of their newborns. Methods: Qualitative research carried out in a teaching hospital in the Northeast Region of Brazil. The patients were followed longitudinally during prenatal care, at birth and during the puerperium. The participants were pregnant women during normal risk prenatal care, aged over 18 years old. Structured and semi-structured interviews were carried out in the prenatal period, participant observation at the time of delivery and new interviews in the puerperium. Content analysis was applied in the thematic modality. Results: 18 women between 21 and 38 years old were enrolled in the research. Women expressed the desire for skin-to-skin contact and breastfeeding as immediate practices right after delivery and birth. However, many women did not believe it was possible, and the performance of routine procedures was considered the main obstacle. These expectations that skin-to-skin contact and early breastfeeding would not be carried out were confirmed in the experiences immediately after birth. Conclusions: The expectations and experiences brought by these women suggest a flaw that starts in prenatal care and implies difficulties in implementing the studied practices. Thus, the empowerment and participation of women can become an important tool in the humanization of birth.